Analiza comparativă a puterii de cumpărare a veniturilor din România și din alte țări europene - Mihăilescu, Adina (Calitatea Vieții, 2014)
Based on the concept of “good society” which was presented at the International Conference “Towards a better society. European Perspective”, the article aims to present a minimum consumption model, but also a view on the purchasing power of the minimum wage from EU′s countries in the Romanian economy. The paper highlights the importance of measuring realistic consumption pattern of poverty in a country or in a certain period of time, and of course, measures can be taken to mitigate the fall into poverty, to support vulnerable population groups and the cost estimates required for the satisfaction of urgent needs. The perspective that we want to present is that we can compare the most important and widely used types of wage income: the average and the minimum wage of the population, in different European countries, on the Romanian market, from this perspective, projecting the purchase of various food products and services with the income of the employees working in the European community. This comparative picture is more suggestive, as the whole world, including the European Union, was affected, for several years, by economic and financial difficulties, and which affected also countries where people’s lives are equal to the welfare concept.